Concept of Islamic Education Perspective KH. Ahmad Dahlan and Buya Hamka (Comparative Study) - Nur Sahlul Mubarok; Muhammad Wildan Shohib; Hafidz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the concept of Islamic education from the perspective of two important figures in the history of Islamic education in Indonesia, namely KH. Ahmad Dahlan and Buya Hamka. Through a comparative study approach, this article aims to identify similarities and differences in the educational views and practices held by the two figures. KH. Ahmad Dahlan, founder of Muhammadiyah, is known for his modern and progressive educational concept, which integrates religious knowledge with general knowledge. Meanwhile, Buya Hamka, a Muslim scholar, writer and thinker, emphasized the importance of morals and spirituality in education. This research uses qualitative methods with descriptive analysis to explore the thoughts and works of these two figures, including their writings, lectures and educational practices. The results of the study show that although there are differences in their approaches, they both have the same goal, namely to form Muslim individuals who are faithful, knowledgeable and have noble character. It is hoped that this article can contribute to the development of Islamic education in Indonesia by integrating the values promoted by these two figures.